Outbreak of Intermediate Species Leptospira venezuelensis Spread by Rodents to Cows and Humans in L. interrogans –Endemic Region, Venezuela - Caraballo, Lizeth (2024)
Leptospirosis is a common but underdiagnosed zoonosis. We conducted a 1-year prospective study in La Guaira State, Venezuela, analyzing 71 hospitalized patients who had possible leptospirosis and sampling local rodents and dairy cows. Leptospira rrs gene PCR test results were positive in blood or urine samples from 37/71 patients. Leptospira spp. were isolated from cultured blood or urine samples of 36/71 patients; 29 had L. interrogans, 3 L. noguchii, and 4 L. venezuelensis. Conjunctival suffusion was the most distinguishing clinical sign, many patients had liver involvement, and 8/30 patients with L. interrogans infections died. The Leptospira spp. found in humans were also isolated from local rodents; L. interrogans and L. venezuelensis were isolated from cows on a nearby, rodent-infested farm. Phylogenetic clustering of L. venezuelensis isolates suggested a recently expanded outbreak strain spread by rodents. Increased awareness of leptospirosis prevalence and rapid diagnostic tests are needed to improve patient outcomes.